Analysis of the Influence of Institutional Ownership and Managerial Ownership on Firm Value with the Proportion of Independent Board of Commissioners as a Moderating Variable - Surya, Tiara Lilis; Abdallah, Zachari; Zano, Jovan Agnistio (The Future of Education Journal, 2024)
This research aims to examine the influence of institutional ownership and managerial ownership variables on company value with the proportion of independent board of commissioners as a moderating variable PT. Akasha Wira I for the 2013-2022 periode. The results of this research show that institutional ownership has no effect on company value with a regression coefficient value for the institutional ownership variable of -10,588. The calculated t value is -632 with a significance level of 547>0.05. Managerial ownership has a positive and significant effect on company value with a regression coefficient value for the managerial ownership variable of -49,678. The calculated t value is-1,815 with a significance level of  112>0.05. The proportion of the board of commissioners is unable to moderate the influence of institutional ownership on company value with the t table value (-1,489<2.03693) with a significance level of -1,847>0.05. The proportion of the board of commissioners is unable to moderate the influence of managerial ownership on company value with a calculated value <t table(-1,489<2.03693) with a significance level of 0,88<0.05.